PENGARUH PEMBERIAN MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PERAWAT PADA RUMAH SAKIT DAERAH MADANI PEKANBARU - Peli Sundari (Politeknik Bisnis Indonesia, 2023)
This research was conducted at the Pekanbaru Madani Regional Hospital. The purpose of this study was to determine the effect of providing work motivation and work discipline on the performance of nurses at the Pekanbaru Madani Regional Hospital. Giving Work Motivation and Work Discipline is determined to be the independent variable (X) while Performance is determined as the dependent variable (Y). The methodology used in this research is descriptive quantitative research to analyze the data collected through a questionnaire (questionnaire). Sources of data in this study came from primary data obtained from questionnaires and secondary data from observational data of research objects. The sample in this study was 47 respondents from the entire population using total saturation sampling method. The data obtained from the questionnaires were tested statistically with the SPSS version 22.0 program. The results showed that giving work motivation (X1) had a positive and significant effect on performance, work discipline (X2) had a positive and significant effect on performance, and giving work motivation and work discipline had a significant effect on performance.